Eco-Friendly Entrepreneurship and Innovations: The Impact of Energy-Efficient Technologies on Business Practices - Sobko, Olha; Boichyk, Iryna; Smereka, Svitlana; Maslosh, Olha; Naumenko, Mariya (Journal of Ecohumanism, 2024)
This article aims to study the impact of energy-saving technologies on business processes in the context of green entrepreneurship and innovation, analysing their implementation and interconnection with efficiency, sustainability, and competitiveness. During the article's writing, general scientific methods of cognition were applied, namely the analysis of literary sources, statistical data, methods of systematisation and generalisation, and comparative analysis. For the research, a survey of 24 experts in ecology and energy, including professors and associate professors from NTU “Dnipro Polytechnic” and the Ukrainian State University of Chemical Technology, was conducted. The evaluations were processed by calculating average values using Excel's “AVERAGE” function and correlation analysis using “Pearson's Correlation” in the JASP program. The study showed that implementing energy consumption optimisation (75.25), combined heat and power production (76.67), and energy-efficient materials (78.3) significantly reduces energy costs and enhances the sustainability of production processes. Moreover, the correlation analysis confirms the impact of power generation (r = -0.38; p = 0.067) and replacement of energy equipment (r = -0.3; p = 0.15) on auxiliary business processes, highlighting the importance of these technologies for improving business efficiency. Thus, green entrepreneurship and energy-saving innovations contribute to environmentally friendly production and ensuring long-term competitiveness.